Knowledge and practices regarding tuberculosis among people living with HIV/AIDS - Yadav, D K; Jhal, N; Pokhara, P K; Nagesh, S; Yadav, S; Niraula, S R (Health Renaissance, 2012)
Background: Tuberculosis is a serious public health problem in many developing countries. More than 2 billion people are infected with TB bacilli and annually around 9 million become infected, 1.7 million die due to this disease. TB is the most common opportunistic infection, leading to the mortality of people living with HIV. Objective: To assess the knowledge and practices of tuberculosis among people living with HIV/AIDS. Method: This study was carried out in Sunsari, Morang and Jhapa district of Eastern Nepal. Face to face interview was performed using convenience sampling technique. Data was collected from people living with HIV/AIDS, related to information on socio-demographic profile, knowledge, practices and risk taking behavior with the help of pretested semi-structured questionnaire. The generated data were entered into Microsoft Excel and SPSS 15.0 and Chi-square was applied for test of significance. Results- The total of 242 subjects were enrolled in the study. Out of them, 75.2% were males and 24.8% females, the age of the respondents varied from 14-65 years. Among them 53.3% were Intra Venus drug users, followed by 17.4% clients of commercial sex workers and housewives (17.4%). Around half (48.8%) of the study population were in the 30-39 yrs age group. The knowledge of tuberculosis disease was satisfactory but in depth knowledge of symptoms was not adequate. Regarding symptoms of TB, it was found that 85% were aware that cough for more than 2 weeks was suggestive of TB, 54% knew of chest pain and 84% knew of haemoptysis. Over the years, perception about tuberculosis has changed, which was shown by our finding, 93% of the respondents knew that TB is curable and 75% knew that anti-tuberculosis drugs provided free of cost under directly observed treatment short course (DOTS). Regarding knowledge of consequences of incomplete treatment, it was found that 17% answered the disease may attack again, and very few (2%) knew that incomplete or discontinued treatment would develop Multi drug resistantance. Conclusion- Our study revealed that knowledge and practices of people living with HIV/AIDS is not adequate. Their knowledge regarding consequences of treatment, and multi drug resisistance was very poor. Thus there is a need for an awareness program regarding tuberculosis - its signs and symptoms, treatment regimen and drug compliance through advocacy, communication and social mobilization. DOI: http://dx.doi.org/10.3126/hren.v10i2.6578 Health Renaissance 2012; Vol 10 (No.2); 118-125